The Influence of Digital Marketing on The Income of Micro, Small, and Medium Enterprises (msmes) at The Food Court of Grand City balikpapan - Agustin, Kety Lulu; Apriani, Endang Sri; Sari, Dessy Handa; Khairiyah, Nurul Musfirah (Trunojoyo University of Madura, 2025)
Nowadays, many marketing methods utilize digital media, including social media, marketplaces, and websites. The purpose of this study is to determine whether digital marketing influences the revenue of Micro, Small, and Medium Enterprises (MSMEs) at the Grand City Balikpapan Food Court and how this influence occurs. This type of research is descriptive mixed method research. The data source in this study is primary data, namely data sourced directly. Then the data is processed using SPSS with simple regression analysis techniques. The results of this study show that digital marketing has a significant effect on revenue. This means that if digital marketing runs well and is used as efficiently as possible, it will increase the number of consumers and will certainly increase the revenue of the MSME. Digital marketing can expand the marketing reach of MSMEs so that they can add consumers to the MSME. With the increase in consumers, it can certainly increase the revenue of Micro, Small, and Medium Enterprises (MSMEs) at the Grand City Balikpapan Food Court. The interview results also confirmed that digital marketing helps increase revenue. Meanwhile, the obstacle is that not everyone has access to digital marketing.